Spatial Distribution and Abundance of Mesopelagic Fish Biomass in the Mediterranean Sea - Clavel-Henry, Morane; Piroddi, Chiara; Quattrocchi, Federico; Macias, Diego; Christensen, Villy (Frontiers in Marine Science, 2020)
Mesopelagic fish, being in the middle of the trophic web, are important key species for the marine environment; yet limited knowledge exists about their biology and abundance. This is particularly true in the Mediterranean Sea where no regional assessment is currently undertaken regarding their biomass and/or distribution. This study evaluates spatial and temporal patterns of mesopelagic fish biomass in the 1994 – 2011 period. We do that for the whole Mediterranean Sea using two well-established statistical models, the Generalized Additive Model (GAM) and Random Forest (RF). Results indicate that the bathymetry played an important role in the estimation of mesopelagic fish biomass and in its temporal and spatial distribution. The average biomass over the whole time period reached 1.08 t/km2 and 0.10 t/km2, depending on the model considered. The Western Mediterranean and Ionian Seas were the sub-regions with the highest biomass, while the Adriatic was the area with the lowest. Temporal trends showed different trajectories with steep decrease and a fluctuation, using respectively RF and GAM. This study constitutes the first attempt to estimate the biomass and the spatial temporal patterns of mesopelagic fish using environmental variables as predictors. Given the growing interest in mesopelagic fish, our study sets a baseline to further develop mesopelagic fish biomass assessments in the region. Our results stress the need to improve data collection and quality in the region while identifying appropriate tools to better understand and assess the processes behind mesopelagic fish dynamics in the basin.